Pembelajaran Non Formal Berbasis Augmented Reality untuk Meningkatkan Hasil Belajar Siswa Inklusi - Sugiyanto, Sugiyanto; Pintakami, Lintar Brillian; Sukesi, Keppi; Nurhadi, Iwan; Fitriana, Yusti Dian (Penerbit Goodwood, 2023)
Purpose: The research objectives were to determine the implementation of augmented reality in revitalizing inclusive education, applying non-formal learning patterns based on augmented reality technology, and analyzing the responses of inclusive students to learning media based on augmented reality technology. Method: The implementation method is through outreach, training, and mentoring. Purposive location determination at SMP Negeri Pasuruan City. The research and development method uses the 4-D development model. The data analysis technique used is descriptive qualitative and Likert analysis. Result: The results of the study of 25 variables revealed that in the small group trials, the variables of interest, motivation, media display, and mastery were the variables that had the highest scores with an average score of 4.6. Whereas in the large group trial there were 5 variables that had the highest score on the media practicality indicator, with a value of 5.0 for each variable. Conclusion: From the results of the study it can be concluded that learning innovations for inclusive students today must make better use of existing information technology. Limitation: The limitation of the research encountered is that the Augmented Reality learning process has not been fully implemented in the form of team teaching so that data collection on student responses needs to be carried out several times. Contribution: The contribution of this research is useful for identifying the needs of students for inclusion in the learning process. So that the Augmented Reality Technology Simulation is able to foster personal independence and entrepreneurial value from potential students